Anti Inflammatory, Analgesic and Antipyretic Activity - Venkataraman, S (International Journal of Pharmaceutical & Biological Archive, 2010)
The pharmacological and chemical constituents of plants from the plant Pergularia daemia Forsk which is widely used in folk medicine. In the present study, the analgesic, antipyretic, anti-inflammatory of Petroleum ether and Chloroform extract of plant of Pergularia daemia Forsk were studied .The analgesic activity was found out by eddy’s hot plate method by using standard Diclofenac sodium . The antipyretic activity was found out by yeast induced pyrexia method by using standard Paracetamol. The anti-inflammatory activity was found out by Carragenan induced paw edema method by using standard Diclofenac sodium. Preliminary phyto chemical screening showed the presence of glycosides, alkaloids, phytosterols, saponins, fixed oils and fats, flavonoids and coumarins are present in extracts. In carrageenan induced paw odema method the chloroform extract of pergularia daemia showed more significant inhibition than petroleum ether extract. The results were found to be highly significant (p<0.01) in comparison to the control. In eddys hot plate method the chloroform extract of pergularia daemia exhibited significant analgesic activity than petroleum extract. In antipyretic activity the chloroform and pet ether both extracts having significant activity.